The sustainability of the producer group concept to the empowerment of smallholder farmers in Chivi District - Marangwanda, Jacob (2017)
Smallholder farmers grappled with challenges of abject poverty, they have been vulnerable to shocks of droughts/floods due to environmental climatic change, lack of agricultural inputs and markets; contributing to untold food insecurity and suffering among producer groups. Chivi has become a donor dependent district for relief and development programs. The producer group model has been employed by development agencies to amalgamate smallholder farmer in Chivi district and ameliorate their livelihoods. The model was implemented as a development vehicle so that farmers could utilise their capabilities, and available assets; interacting with institutions so as to access inputs, knowledge and markets which in turn boosted production of value chains. The livelihoods outcomes realised included income increase and improve food security: the overall goal of the model. Although the model celebrated some level of achievements,other variables like global warming and climate change acted as major hurdle to ultimate food security.